The Representation of Female Authority in Maleficent: Mistress of Evil's (2019) - Imelda Aulia Arif; Masnia Rahayu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The representation of female authority in films has often been tied to questions of empowerment, leadership, and gendered expectations. However, few studies analyze how authority is constructed through both verbal and non-verbal performance, particularly within conflict-driven cinematic narratives that foreground leadership styles rather than empowerment alone. This study examines Maleficent: Mistress of Evil (2019) using Judith Butler’s theory of gender performativity and Eagly and Karau’s role congruity theory to explore how female authority is performed through dialogue and expression. The research applies a qualitative narrative analysis, specifically through close textual analysis of selected scenes, dialogues, and visual expressions that foreground moments of leadership and power negotiation among female characters. The research focuses on Maleficent, Aurora, and Queen Ingrith as central figures of authority. The findings reveal that Maleficent embodies transformative guardianship, Aurora demonstrates inclusive and collaborative leadership, and Queen Ingrith represents authoritarian domination. Authority in the film is thus constructed not as a fixed trait but as a performance enacted through words, gestures, and presence. This study contributes to feminist film criticism by highlighting the complexity of female authority beyond empowerment discourse, showing how cinematic performance mirrors, the challenges faced by women leaders in political and social contexts, and underscoring the significance of recognizing diverse and ethically grounded models of female leadership.